Emphysematous Pyelonephritis Following Ureterovesical Reimplantation for Congenital Obstructive Megaureter. Pediatric Case Report and Review of the Literature - Girgenti, Vincenza; Pelizzo, Gloria; Amoroso, Salvatore; Rosone, Gregorio; Di Mitri, Marco; Milazzo, Mario; Giordano, Salvatore; Genuardi, Rosaria; Calcaterra, Valeria (Frontiers in Pediatrics, 2019)
Introduction Emphysematous pyelonephritis (EPN) is a rare, life-threatening necrotizing infection of the kidney. To date, very few cases of EPN have been described in the pediatric age. The first case of EPN in a toddler occurring after ureterovesical reimplantation for congenital obstructive megaureter is reported with a literature review. Case report a 23-month-old male, with a prenatal diagnosis of obstructive megaureter and incomplete duplication of the left urinary tract, was admitted to our Unit where he underwent surgery to treat increased dilatation of the renal pelvis and appearance of an obstructive curve. The latter was revealed at renal scintigraphy, the exam highlighted the radiographic aspect of the cortical renal parenchymal sufferance. At admission preoperative exams were normal, and no recurrent urinary tract infections were documented. Surgical removal of the left stenotic ureteral common tract of the incomplete duplex collecting system was accomplished; ureterovesical reimplantation was performed without ureteral recalibration. No intraoperative complications were recorded. In the immediate postoperative period, urosepsis and the patient’s lethargic condition led to life-threatening conditions requiring urgent admission to the intensive care unit. Biochemical analysis showed leukocytosis, anemia, increased C-reactive protein, prolonged prothrombin time, pancytopenia, hyponatremia. Abdominal sonographic evalutation revealed the presence of gas in the left kidney. Unilateral EPN (Class 2) was confirmed by CT- scan. Escherichia coli was cultured from peripheral blood and antimicrobial therapy was started. No additional interventions were required. The child was discharged 14 days postoperatively with normal renal function. Conclusion EPN is a serious condition that can occur after surgical treatment for urinary tract obstruction. Early detection of air in the kidney should be considered a sign of complicated urinary tract infection. Immediate aggressive resuscitation and antimicrobial therapy are effective and curative with a positive outcome.